A study on Digital Marketing for Entrepreneurs - Simarjeet Kaur (AG Volumes, 2022)
An person who accepts the challenge of developing something novel and bringing it to the attention of consumers all over the globe is referred to as an entrepreneur. They are concerned with the conceptualization, developing, and execution of a new company endeavour, in addition to its initial launch. Both the technology behind search engines and the ways in which people use them are always changing and developing. The same is true for companies’ online presences and websites. One day, your website, which was not developed in a manner that is conducive to mobile devices, is functioning well. The next day, a significant shift takes place apparently overnight, and your company’s site traffic and conversions take a significant nosedive. As more time has passed, it has become abundantly clear that adhering to the conventional methods of marketing alone is not sufficient to get the desired results. In today’s hypercompetitive business environment, it is essential to actively advertise your company online, regardless of where in the city you choose to establish your company. In addition, company owners now have a greater awareness of their responsibilities as a result of digital marketing. As a result of the fact that the owners of an increasing number of new businesses are also among its first staff members, the term “startup” is becoming more obsolete. As a result, there is no longer the possibility of delegating tasks. There is a feeling of cohesion across their whole company. Entrepreneurs have ingrained in themselves a feeling of personal accountability for both the achievements and difficulties of their companies.